Effect of different fertilization treatments on the growth rate of gracilaria sp / Nurul Afifa Abdul Rahman - Abdul Rahman, Nurul Afifa (2020)
Conway medium has been widely used in microalgae culture as another kind of plant’s supplement, especially for seaweed. Many positive results were observed. This study was conducted to compare the effect of fertilizer treatments and the aeration supply towards the growth of sea plants, Gracilaria sp. The experiment conducted based on three different kinds of fertilizers, which are the Conway medium and another two compounds of urea and NPK fertilizer as one of the treatment and the present of water circulation during algae cultivation. The environment and seaweed parameters were measured daily together with the growth rate of the Gracilaria sp. cultured in six days experimental period. The data obtained were analyzed using Two-way ANOVA. Generally, in the cultivation of seaweed without aeration, water treatment with Conway media gives an upbeat impression with the best percentage of Daily Growth Rate (DGR) per day (>2%). While in the cultivation without aeration, urea was recorded to give the highest growth rate among the other fertilizer treatments. This concluded that both treatments of fertilizers and aeration system play important roles in micro and macroalgae cultivation. The nutrients contained in each of the fertilizer treatments and also the parameters and external factors that contributed to the increasing or decreasing of the DGR value. In the end, this study shows the ability of three different fertilizer treatments on Gracilaria sp. to sustain the growth rates among the higher measured for outdoor cultures.